PERANCANGAN SISTEM INFORMASI LOCATION BASED SERVICE (LBS) OBJEK WISATA MENGGUNAKAN METODE INKREMENTAL BERBASIS ANDROID DI KOTA BEKASI - Fitriyani, Aida; Lubis, Hendarman; Hendharsetiawan, Andy Achmad (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Tourist attractions are a necessity for people to go on holiday with their families. Tourist attractions in Bekasi also have great potential for regional income if they are managed well. Data from the Central Statistics Agency (BPS) shows that the population of Bekasi Regency currently reaches 3.3 million people and Bekasi City 2.6 million, an increase of around 1 million in the last 5 years. In the modern era, technology is developing so rapidly that it has become one of society's main needs. Technology that is always developing, such as smartphones and Android, can be easily utilized in carrying out various activities. Location Based Service (LBS) is a location service that uses GPS (Global Positioning Service) which functions to find a destination location to make it easier for users. Many people travel to a certain place to enjoy their holiday, this is a necessity in life to refresh the mind while working or studying. For this reason, it is necessary to present an information system that provides tourist attraction location services to make it easier for people to find these tourist attractions. The Location Based Service (LBS) information system can help the public in showing directions. This information system can help the public to carry out holiday activities to tourist attractions. This Location Based Service (LBS) system provides information services regarding tourist attractions and travel preparation tips. This tourist attraction's Location Based Service (LBS) system is also equipped with a location route feature.